2012
DOI: 10.1177/0022034512449465
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Caries Prevention and Control

Abstract: Modulation of the microbiota for restoring and maintaining health is a growing issue in medical science. A search for relevant clinical trials on the use of probiotic bacteria as a potential and clinically applicable anti-caries measure was performed. According to predetermined criteria, papers were selected and key data on study design, sample size, intervention, duration, and results were extracted. Two animal and 19 human studies were retrieved. Most studies were short-term and restricted to microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 28 publications
2
76
1
2
Order By: Relevance
“…Probiotics have traditionally been associated with gut health; however, over the last decades an increasing number of potential applications for oral health have been suggested [for reviews, see Twetman and Stecksén-Blicks, 2008;Twetman and Keller, 2012]. The mode of action is attributed to three main avenues: probiotic bacteria can prevent or inhibit the proliferation of pathogens, suppress production of virulence factors by pathogens, and…”
Section: Copyright © 2013 S Karger Ag Baselmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics have traditionally been associated with gut health; however, over the last decades an increasing number of potential applications for oral health have been suggested [for reviews, see Twetman and Stecksén-Blicks, 2008;Twetman and Keller, 2012]. The mode of action is attributed to three main avenues: probiotic bacteria can prevent or inhibit the proliferation of pathogens, suppress production of virulence factors by pathogens, and…”
Section: Copyright © 2013 S Karger Ag Baselmentioning
confidence: 99%
“…Studies have clearly shown that selected probiotic strains and clinical isolates can inhibit the growth of mutans streptococci (MS) in vitro [Simark-Mattsson et al, 2007;Hasslöf et al, 2010;Keller et al, 2011;Söderling et al, 2011]. In vivo, a short-term reduction in MS counts has been observed with Lactobacillus reuteri [Caglar et al, 2006] and L. rhamnosus [Glavina et al, 2012]; however, any clinical recommendation for an oral health purpose is not yet justified [Haukioja, 2010;Twetman and Keller, 2012].…”
mentioning
confidence: 99%
“…In addition, numerous small molecules, including tt-farnesol (12), chitosan, 7-epiclusianone (13), and apigenin (14), have been characterized and have been shown to have antibiofilm activity. Other potential anticariogenic methods include sugar substitutes (15), probiotic strains (16), and arginine (17). However, few of these treatments have been proven to confer selectivity against S. mutans biofilms.…”
mentioning
confidence: 99%
“…There are a number of reviews of the effect of probiotic bacteria on the oral microbiota and how this may affect dental caries and periodontal disease [Stamatova & Meurman, 2009;Bonifait L et al, 2009;Twetman & Keller, 2012;Twetman, 2012]. Several studies have shown positive effects of probiotic lactobacilli: reduction in the number of mutans streptococci, dental plaque and gingival inflammation [Nikawa et al, 2004;Krasse et al, 2006;Calgar et al, 2008;Marttinen et al, 2012].…”
mentioning
confidence: 99%